Digitalization of public services: modeling and monitoring of efficiency - I. Yu. Bogdanovsky (Путеводитель предпринимателя)
The article examines the concept of digitalization of public services, defines the target guidelines for this process taking into account the practice of the last decade of providing public services to the population in Russia and trends in the development of their technological forms of implementation online. The parameters that can be changed in relation to the digital process of providing public services both statically and dynamically are determined, and directions for their use for calculating economic efficiency are proposed. An attempt was made to develop a holistic pattern for modeling an economically efficient process of digitalization of public services, both positive and negative factors in terms of economic efficiency were identified, which can be identified and used in combination to quantitatively assess the effectiveness of digitalization of public services. Considerable attention in the scientific article is paid to the problems of the historical evolution of the digital model of organizing public services in Russia with the definition of qualitative and quantitative results achieved in the framework of the transformation of the super platform «Gosuslugi» from a local tool for transferring part of the offline services to the online format into the central platform for interaction of the triad state – business – citizens.